Effects of legislation restricting pack sizes of paracetamol and salicylate on self poisoning in the United Kingdom: before and after study. Issue 7296 (19th May 2001) - Hawton, Keith; Townsend, Ellen; Deeks, Jonathan; Appleby, Louis; Gunnell, David; Bennewith, Olive; Cooper, Jayne
Abstract: Objective: To evaluate the effects on suicidal behaviour of legislation limiting the size of packs of paracetamol and salicylates sold over the counter. Setting: UK population, with detailed monitoring of data from five liver units and seven general hospitals, between September 1996 and September 1999. subjects: People who died by suicidal or accidental overdose with paracetamol or salicylates, or who died of undetermined causes; patients admitted to liver units with hepatic paracetamol poisoning; patients presenting to general hospitals with self poisoning after taking paracetamol or salicylates. Main outcome measures: Mortality from paracetamol or salicylate overdose; numbers of patients referred to liver units or listed for liver transplant; numbers of transplantations; numbers of overdoses and tablets taken; blood concentrations of the drugs; prothrombin times; sales to pharmacies and other outlets of paracetamol and salicylates. Results: Numbers of tablets per pack of paracetamol and salicylates decreased markedly in the year after the change in legislation on 16 September 1998. The annual number of deaths from paracetamol poisoning decreased by 21% (95% confidence interval 5% to 34%) and the number from salicylates decreased by 48% (11% to 70%). Liver transplant rates after paracetamol poisoning decreased by 66% (55% to 74%). The rate of non-fatal self poisoning with paracetamol in any form decreased by 11% (5% to 16%), mainly because of a 15% (8% to 21%) reduction in overdoses of paracetamol in non-compound form. The average number of tablets taken in paracetamol overdoses decreased by 7% (0% to 12%), and the proportion involving >32 tablets decreased by 17% (4% to 28%). The average number of tablets taken in salicylate overdoses did not decrease, but 34% fewer (2% to 56%) salicylate overdoses involved >32 tablets. After the legislation mean blood concentrations of salicylates after overdose decreased, as did prothrombin times; mean blood concentrations of paracetamol did not change. Conclusion: Legislation restricting pack sizes of paracetamol and salicylates in the United Kingdom has had substantial beneficial effects on mortality and morbidity associated with self poisoning using these drugs.